Collaboration of the Three Centers of Education in Implementing a Home-Based Qur’anic Reading Control Program and Its Implications for Students’ Qur’anic Literacy - Firmansyah Firmansyah; Ilham Ilham; Ahmadin Ahmadin (Borneo Research and Education Center, 2026)
This study examines the collaboration of the three-center education system consisting of family, school, and community in the implementation of a home-based Qur’anic reading control program and its contribution to improving students’ Qur’anic literacy. The study addresses three main issues, namely how collaboration is structured and implemented, how the program improves students’ reading ability, and what factors support and hinder its implementation. This research uses a qualitative descriptive approach with data collected through observation, interviews, and documentation involving teachers, students, parents, and community members. Data were analyzed through data reduction, data display, and conclusion drawing. The findings show that collaboration is systematically organized through clear role distribution, continuous communication, and the use of a reading control book as a monitoring tool. The program significantly improves students’ Qur’anic literacy in terms of reading fluency, pronunciation accuracy, application of tajwid, and consistency in reading habits. In addition, the program fosters discipline and intrinsic motivation among students. The main supporting factors include teacher commitment, parental involvement, and community support through Qur’anic learning activities, while the main inhibiting factors are limited parental time and variations in Qur’anic literacy among parents. The study concludes that structured collaboration supported by a monitoring mechanism is an effective strategy for sustaining Qur’anic literacy development. The implication of this study highlights the importance of integrating home, school, and community roles through continuous supervision to enhance religious literacy in primary education.